2008
DOI: 10.1121/1.2839283
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acoustical conditions for speech communication in working elementary school classrooms

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
110
2
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(136 citation statements)
references
References 18 publications
12
110
2
12
Order By: Relevance
“…Unnormalized speech levels at each position for a 65 dBA direct field at 1 m are shown in Table IV. Level differences were, as in experiment 1, consistent with theoretical predictions ͑Barron and Lee, 1988;Sato and Bradley, 2008͒. It should be noted that without SPL normalization listeners in rooms with ␣ = 0.7 or ␣ = 1.0 could receive speech at levels near 50 dB SPL, a level that has been shown to impair intelligibility for implant users ͑Skinner et al Firszt et al, 2007͒.…”
Section: Materials and Processingsupporting
confidence: 71%
See 2 more Smart Citations
“…Unnormalized speech levels at each position for a 65 dBA direct field at 1 m are shown in Table IV. Level differences were, as in experiment 1, consistent with theoretical predictions ͑Barron and Lee, 1988;Sato and Bradley, 2008͒. It should be noted that without SPL normalization listeners in rooms with ␣ = 0.7 or ␣ = 1.0 could receive speech at levels near 50 dB SPL, a level that has been shown to impair intelligibility for implant users ͑Skinner et al Firszt et al, 2007͒.…”
Section: Materials and Processingsupporting
confidence: 71%
“…For anechoic speech of 65 dBA at 1 m, measured speech levels at the 1, 3, and 4 m positions were 67.7, 64.8, and 63.5 dBA, respectively. These small differences in level as a function of SLD are consistent with theoretical predictions for a classroom of this size ͑Barron and Lee, 1988; Sato and Bradley, 2008͒. All speech signals were subsequently presented to the subjects at 65 dBA, with the level held constant to differentiate the effects of reflection patterns at each position from any effects of level difference.…”
Section: Signal Processingsupporting
confidence: 62%
See 1 more Smart Citation
“…They also proposed a method for estimating SNR values in classrooms when they are occupied and in operation. The results of the active classroom acoustics studies (Hodgson et al, 1999;Sato, Bradley, 2008) indicate greater noise levels than recommended in the ANSI standard for classroom acoustics (ANSI S12.60, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies (Hodgson et al, 1999;Sato, Bradley, 2008) have reported that the speech and noise levels are quite different from values measured in active classrooms with the influence of noise due to students' activity. They also proposed a method for estimating SNR values in classrooms when they are occupied and in operation.…”
Section: Introductionmentioning
confidence: 99%